Quantitative CT measurements of small pulmonary vessels in chronic obstructive pulmonary disease: do they change on follow‐up scans?. (13th November 2014) - Saruya, Shinji; Matsuoka, Shin; Yamashiro, Tsuneo; Matsushita, Shoichiro; Fujikawa, Atsuko; Yagihashi, Kunihiro; Kurihara, Yasuyuki; Nakajima, Yasuo
Summary: The aims of this study were to perform a longitudinal evaluation of the cross‐sectional area (CSA) of small pulmonary vessels and the extent of emphysema measured on computed tomography (CT) scans of patients with chronic obstructive pulmonary disease (COPD), and to correlate the pulmonary vascular measurements with extent of emphysema. The institutional review board approved this retrospective study and waived the need for patients' informed consent. Seventy‐four patients with COPD who underwent both initial and follow‐up CT scans at an interval of ≥12 months were analysed. The CSA of small pulmonary vessels <5 mm 2 was measured, and the percentage of total CSA of the area of the lung (%CSA<5 ) was calculated. The extent of emphysema was assessed as the percentage of low attenuation area (%LAA, <−950 Hounsfield units). Comparisons between initial and follow‐up measurements were performed using the Wilcoxon signed‐rank test. The relationship between longitudinal changes in %CSA<5 and %LAA during the follow‐up period was assessed using the Spearman rank correlation. The %LAA increased significantly on follow‐up CT scans ( P <0·0001). The %CSA<5 was slightly decreased on follow‐up scans, but the difference was not significant. Although longitudinal change in %LAA was positively correlated with duration of follow‐up period (ρ = 0·505, P <0·0001), longitudinal change in %CSA<5 was not. In conclusion, there was a progressive increase in the extent of emphysema over time, but no significant decrease in the CSA of small pulmonary vessels over the same time period.